1995
DOI: 10.1007/bf01837917
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac release of histamine after ventricular fibrillation and defibrillation during insertion of implantable cardioverter defibrillators (ICD)

Abstract: Histamine has inotropic, chronotropic, arrhythmogenic, and vasoactive effects, and is released from the heart in ischaemia-reperfusion injury. The effect of ventricular fibrillation (VF) and defibrillation (DEF) on histamine release was investigated in 9 anaesthetized patients undergoing transvenous implantation of ICD. Concomitant arterial and coronary sinus (CS) blood samples were drawn before induction of VF (duration 20 seconds), immediately after, and 2 and 5 min after DEF (18-24 Joules). Basal arterial h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In addition, there are some data which suggest that cardiac histamine might be released from non-MC stores, too. Early studies of Valen et al showed that ischemia causes a sustained increase in cardiac histamine content [28,29], and similarly, Dai et al demonstrated an increase in histamine content in the right ventricle with unchanged cardiac MC numbers during acute myocardial ischaemia [30]. These results may indicate that non-MC sources are also involved in cardiac histamine liberation.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, there are some data which suggest that cardiac histamine might be released from non-MC stores, too. Early studies of Valen et al showed that ischemia causes a sustained increase in cardiac histamine content [28,29], and similarly, Dai et al demonstrated an increase in histamine content in the right ventricle with unchanged cardiac MC numbers during acute myocardial ischaemia [30]. These results may indicate that non-MC sources are also involved in cardiac histamine liberation.…”
Section: Discussionmentioning
confidence: 93%